Pengaruh Ethyl Methane Sulphonate (EMS) Terhadap Pertumbuhan dan Variasi Tanaman Marigold (Tagetes sp.) - NI MADE DIAN PRATIWI; MADE PHARMAWATI; IDA AYU ASTARINI (Fakultas Pertanian Universitas Udayana, 2013)
The Effect of Ethyl Methane Sulphonate (EMS) on Growth and Variations of Marigold (Tagetes sp.) The aims of this research are to determine the variation of marigold (Tagetes sp) derived from seed treated with EMS and to recommend the EMS concentrations that are able to induce varietion. Seeds of marigold cv Narai Orange were soaked in water for 6 hours, followed by soaking in EMS at concentration of 0%, 0.3%, 0.6% and 0.9% for 4 hours. This study employed Randomized Complete Blok Design with 10 replicates and each replicate consisted of 10 plants. Six plants were randomly chosen for measurements. The total number of samples observed were 240 plants. Observations were made on the percentage of the growth, plant height, number of leaves, number of branches, diameter and weight of flowers. Data obtained from the observations were analyzed using Analysis of Variance (ANOVA), followed by DMRT (Duncan’s Multiple Range Test) if there is a significant difference between treatments. The EMS treatment reduced all characters observed. The EMS concentration of 0.6% showed plant that had yellow flowers. The 0.9% EMS treatment resulted in one plant with chimera, 6 dwarf plants, 2 plants with thin stems, and 1 short plant with many branches. Untreated plants did not show any variation.